Undergraduates' Use of Internet of Things (IoT) Technologies in the Classroom in Ondo State, Nigeria - Ayelaagbe, Sina Opeoluwa (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
The Internet of Things (IoT) is a technological revolution that enables pervasive interaction between objects people and environments. The study investigated undergraduates' usage of the Internet of Things in the classroom in Ondo State, Nigeria. The descriptive survey was adopted for this study. The population comprised all undergraduates in the universities in Ondo State; the respondents were selected using clusters while a simple random sampling technique was used to select universities. The sample size consisted of 250 undergraduates selected from the three universities. The objectives of the study were to identify the most used IoT Technologies investigate the impacts derived by undergraduates' and identify the challenges and threats of using IoT in the classroom. Three (3) research questions were raised and answered. The title of the questionnaire used for the collection of data is Undergraduates' Usage of Internet of Things (UUOIoT)" Three experts from the Department of Educational Technology University of Ilorin, Kwara State, Nigeria validated the instrument to ensure content and face validity of the instrument. Cronbach's Alpha was used to find out the value of the reliability of the instrument and it yielded 0.78. Data collected were analysed using percentage, mean, and standard deviation to answer the research questions raised. The study concluded that tablets and mobile devices were mostly used and undergraduates benefit maximally from using IoT. It was recommended that undergraduates and lecturers should make adequate use of IoT for keeping records and their artworks.